PENGARUH INFORMASI LABA, ARUS KAS DAN SIZE PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nurdiana, Diah (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
This research aims to know the influence of net profit, cash flow, and the size of the company against the return of shares in food and beverage companies listed on the Indonesia stock exchange (idx) either partially or simultaneous. In this study used methods of empirical research. The variables examined, namely net profit, operating cash flow, cash flow, cash flow investment funding, the size of the company and the return of shares. The population used in this study are food and beverage companies listed on the Indonesia stock exchange (idx) as many as 12 companies. Data collection techniques in the study done by examination of the documents tracing the companys financial reports, namely food and beverage in 2010-2014 in BEIs official website (www.idx.com). The results of the research that havedone, then multiple linear regression equation is obtained as follows: Å¶ = 0,266418 â 0,065069 X1 - 0,008726 X2 â 0,011104 X3 X4 + 0.458 X5. A classic assumption test results it can be concluded that the Gaussian normality test, does not occur multikolinieritas, heteroskedatisitas not happened and there does not occur autokolerasi positive or negative, then the regression model BLUE (Best Linear Unbiased Estimator) have been done. Testing the hypothesis partially independent variables indicating that the size of the stock return of influential companies, while the other independent variables showed no effect on stock return. From the results of the calculations through eviews 8 can be seen that the value of F is calculated values 0,04078.. Thus that variables namely net profit, operating cash flow, cash flow, cash flow investment funding, and total assets are jointly significant effect against the return of shares.Â The results of the analysis of the coefficient determination R2 is 0,188660 .This means the influence of the variable net profit, operating cash flow, cash flow, cash flow investment funding, and total assets against the return of shares is 18,87 %, while the remainder (100% - 18,88 % = 81,12%)Â can be explained by other free variables such as cash dividends.Â The results of the analysis of the obtained number R of 0,3734 then compared with the value of the correlation coefficient interpretation table 0,3734 been 0,20 â 0,400 this indicates that the relationship between the dependent variable against the independent variable is weak